A non-invasive heart rate measurement system using laser Doppler blood flowmetry with husbandry training of the masked palm civet (Parguma larvata). (16th April 2021) - Nogami, Hirofumi; Ohgata, Satoru; Saito, Aya; Ban, Kazuyuki; Akiyama, Terukazu; Hiejima, Takumi; Takigawa, Ryo; Hosoya, Tadatsugu
Abstract: Husbandry training (HT) is done to facilitate healthcare, treatment or animal research with zoo animals. At the Omuta City Zoo, HT of masked palm civets ( Parguma larvata ) is used to aid the taking of blood samples. With HT the burden on the animal can be remarkably reduced without the use of anesthesia. However, it is necessary to devise a blood sampling method using HT that reduces stress on the animals as much as possible. To devise such a stress-reducing method, quantitative assessments related to stress are needed. As heart rate increases with stress, we attempted to devise a non-invasive method for measuring heart rate. The attachment of sensors not only stresses the animal but also requires much effort from keepers. Therefore, a laser Doppler blood flowmeter (LDF) was embedded in the HT board, and an LDF and an algorithm to eliminate body motion artifacts were used in measurement attempts. As a result, a clear pulse wave was detected in some sections, and heart rate was calculated from the pulse wave.